Targeting Aurora A Kinase (AAK) in Platinum-Resistant High Grade Serous Ovarian Cancer - Ganapathi, Ram N.; Norris, Eric J.; Sutker, Ashley P.; Klotz, Kaitlin E.; Ganapathi, Mahrukh K. (Frontiers in Oncology, 2020)
Aurora A kinase (AAK) involved in G2-M transition is functionally involved in centrosome maturation and maintaining an active spindle assembly checkpoint. We tested the hypothesis that in platinum-taxane resistant high grade serous ovarian cancer (HGSOC) inhibition of AAK involved in G2-M transition would enhance the anti-tumor activity of cisplatin (CP) or paclitaxel (PT). Using HGSOC cell lines from platinum-taxane refractory patients that do not harbor BRCA1/2 mutations, we tested the anti-tumor activity of CP, or PT alone or in combination with the AAK inhibitor alisertib (AL). Treatment with CP for 3 h or PT for 6 h followed sequentially by AL for 48 h led to a significant decrease in cell survival (p < 0.001) compared to treatment with either drug alone in HGSOC cells but not in immortalized normal human ovarian surface epithelium or normal human fallopian tube secretory epithelium cells. The treatment with CP or PT followed by AL also led to a significant increase in reactive oxygen species (p < 0.05), apoptosis (p < 0.001) and accumulation of cells in G2/M that was accompanied by a modest increase in expression of AAK. Downregulation of AAK, but not aurora B kinase, with targeted siRNAs also significantly enhanced apoptosis by CP or PT, suggesting that AL specifically targeted AAK. In summary, in HGSOC without BRCA1/2 mutations, CP, or PT resistance can potentially be circumvented by sequential treatment with AL that inhibits AAK involved in G2-M transition.